Consistent Outperformance Based on Published Information – or When Reality Defies Theory. Issue 78 (July 2015) - Herrera, Gabriel; Toivanen, Tero
<x xml:space="preserve">Abstract</x> Successful active management is widely accepted to be a difficult undertaking, as financial markets are believed to be fairly efficient. Achieving outperformance based on publicly available historical information is seen as impossible, according to financial markets theory. Therefore, all the more surprising are our findings that a systematic investment process selecting 'superior' companies based on published fundamental company data leads to sustained outperformance